Clinical and microbiological profile of pneumonia in severe acute malnourished children - Shukla, Omprakash; Dave, Reema; Doshi, Rajkumar Prakashbhai (International Journal of Research in Medical Sciences, 2017)
Background: It is estimated that 57 million children are underweight (moderate and severe) in India. More than 50% of deaths in 0-4 years are associated with malnutrition. Pneumonia is common in malnourished children and is frequently associated with fatal outcome, especially in children younger than 24 months of age. The aim and objectives was to evaluate the clinical and microbiological profile of pneumonia in severe acute malnourished children. Methods: A cross sectional study was carried out on 60 severe acute malnourished children admitted at Department of Pediatrics, SSG Hospital Vadodara. Results: Most of the admitted children belonged to rural and tribal areas (81.7%). Children in the age group of 1-3 years were more prone to develop very severe pneumonia (51.7%). Blood culture yield was 80%. Most common isolate was Staphylococcal Aureus which was isolated in 16.6% of the patients. Conclusions: We concluded at the end of the study that malnourished children were prone to develop more severe pneumonia, required aggressive antibiotic usage as the causative organisms were strikingly different as compared to well-nourished children and needed a longer hospital stay.